Evaluation of Diabetes Self-Management Behavior among type-2 diabetes patients at University Center in Riyadh, Saudi Arabia - A Nursing Study (Asian Journal of Pharmaceutics (AJP), 2023)
Background and Objective: Diabetes is a chronic endocrine disease, which requires self-care from experiencedhealth-care professionals such as nurses to obtain a healthy lifestyle. This responsibility requires self-care tomanage their condition and delay diabetes-related complications. Therefore, this study aimed to assess thediabetes self-management behavior and associated demographic factors of Saudi Type 2 diabetes patients in,Riyadh, Saudi Arabia. Methods: A cross-sectional, self-administered questionnaire-based study was conductedat the University Diabetes Center, College of Medicine, King Saud University located in Riyadh, Saudi Arabia.The Diabetes Self-Management Behavior was assessed using a Summary of the Diabetes Self-Care Activitiesquestionnaire-8 which includes two items for general diet, two items for exercise, two items for blood glucosetesting, and two items for foot care. Results: Of the 98 subjects, 48 (49%) were male and 50 (51%) were female.The mean age of the diabetes was 46.0 years (SD = 13.80). The current findings revealed that 18.4% (n = 18)of the respondents followed a healthy eating plan for 7 days in a week, while 19.4% (n = 19) followed 5 daysin a week. Among the respondents, 18.4% (n = 18) of the participants had never participated in any physicalactivities throughout the week, and only 17.3% (n = 17) participated in 30 min of physical activity for 5 daysin a week. The overall mean self-management behaviors were 4.37 days per week (SD = 1.63). The mean scoreof the diet was 4.36 days (SD = 2.38), exercise 3.90 (SD = 2.0), blood sugar testing was 4.59 days (SD = 2.50),while foot care was 4.63 days (SD = 2.71) in the past week. There was no significant association between themean score of the SDCA (F = 0.60, df = 10, P > 0.01). Conclusion: The findings reported very poor selfcarepractice, with respect to physical activity and healthy diet were reported among Saudi diabetic patients.Furthermore, self-management behavior was not significantly associated with the demographic characteristics ofdiabetics. Therefore, consultations with health-care professionals such as nurses help in providing dietary adviceand lifestyle recommendations which may help in glycemic control.